Impact of Coronavirus Pandemic on the Indian Education Sector: Perspectives of Teachers on Online Teaching and Assessments - Joshi, Amit; Vinay, Muddu; Bhaskar, Preeti (Interactive Technology and Smart Education, 2021)
Purpose: In India, the COVID-19 outbreak has been declared an epidemic in all its states and union territories. To combat COVID-19, lockdown was imposed on March 25, 2020 which has adversely affected the education system in the country. It has changed the traditional education system to the educational technologies (EdTechs) model, where teaching and assessments are conducted online. This paper aims to identify the barriers faced by teachers during online teaching and assessment in different home environment settings in India. Design/methodology/approach: Interpretative phenomenological analysis (IPA) of qualitative research methodology has been used in this research. The study was conducted among the teachers working in the government and private universities of Uttarakhand, India. Semi-structured in-depth interviews were conducted among 19 teachers to collect data regarding the barriers faced by them during online teaching and assessment. ATLAS.ti, version 8 was used to analyze the interview data. Findings: The findings revealed four categories of barriers that are faced by teachers during online teaching and assessments. Under home environment settings, a lack of basic facilities, external distraction and family interruption during teaching and conducting assessments were major issues reported. Institutional support barriers such as the budget for purchasing advanced technologies, a lack of training, a lack of technical support and a lack of clarity and direction were also reported. Teachers also faced technical difficulties. The difficulties were grouped under a lack of technical support, it included a lack of technical infrastructure, limited awareness of online teaching platforms and security concerns. Teachers' personal problems including a lack of technical knowledge, negative attitude, course integration with technology and a lack of motivation are identified as the fourth category to damper their engagement in online teaching and assessments. Practical implications: The findings of the study can be helpful to the regulatory authorities and employers of higher education institutions who are planning to adopt online teaching as a regular activity in the future. The insights gained from the findings can help them to revisit their existing policy frameworks by designing new strategies and technical structures to assist their teachers in successfully embracing the EdTech to deal with any crisis in the future. Originality/value: Many authors have conducted research to address the problems faced by students related to online teaching and learning during COVID-19 in India. To the best of the authors' knowledge, this is the first study that addresses the challenges faced by teachers during the online teaching and assessment in the home environment settings by using qualitative analysis (IPA) techniques. The current study replenishes the gap by contributing to the literature of online teaching and assessment under the home environment settings during the pandemic situation.